A Philosophical Analysis of The Process of Revival and Ascension in Spirituality - Uzoqova Gulzoda Bahrom qizi (Scientific Trends, 2025)
This article presents a philosophical analysis of the processes of revival and ascension in spirituality, exploring their metaphysical, epistemological, and existential dimensions. Revival is interpreted as the reawakening of the inner self, often catalyzed by crisis, reflection, or divine encounter, while ascension denotes the progressive elevation of consciousness towards higher states of being or union with the Absolute.
Keywords: Contemplation and worldview, morality and manners, national idea, value, national values, moral values, spirituality, spiritual attitude.